2019
DOI: 10.7554/elife.44860
|View full text |Cite
|
Sign up to set email alerts
|

Liquid-crystal organization of liver tissue

Abstract: Functional tissue architecture originates by self-assembly of distinct cell types, following tissue-specific rules of cell-cell interactions. In the liver, a structural model of the lobule was pioneered by Elias in 1949. This model, however, is in contrast with the apparent random 3D arrangement of hepatocytes. Since then, no significant progress has been made to derive the organizing principles of liver tissue. To solve this outstanding problem, we computationally reconstructed 3D tissue geometry from microsc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(72 citation statements)
references
References 32 publications
4
65
0
Order By: Relevance
“…One usual marker of cell polarity is shape anisotropy( 1 ). Akin to elongated molecules in liquid crystals( 5 ), elongated cells can self-organize into patterns featuring long-range orientational order ( 6 – 9 ). Orientational fields often present topological defects, where the orientational order is ill-defined.…”
Section: Main Textmentioning
confidence: 99%
“…One usual marker of cell polarity is shape anisotropy( 1 ). Akin to elongated molecules in liquid crystals( 5 ), elongated cells can self-organize into patterns featuring long-range orientational order ( 6 – 9 ). Orientational fields often present topological defects, where the orientational order is ill-defined.…”
Section: Main Textmentioning
confidence: 99%
“…Here, we analyze network geometry using a digital reconstruction of the sinusoidal network based on high-resolution image data of adult mouse liver [13,14]. We develop a network generation algorithm that reproduces statistical features of the sinusoidal network (node degree distribution, edge length distribution, mean nematic order parameter), enabling us to simulate arbitrarily sized networks from spatially restricted biological samples and, moreover, to explore in silico a design space of three-dimensional networks.…”
Section: Plos Computational Biologymentioning
confidence: 99%
“…Yet, topology suggests fundamental differences between two-dimensional and three-dimensional spatial networks, as it imposes constraints on the distribution of cycles in the network [12]. Here, we take advantage of recent technological advances in high-resolution imaging of adult mouse liver tissue [13,14], allowing us to study statistical geometry and resilience of three-dimensional sinusoidal networks.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, recent studies demonstrated the importance of nematic organization of actin cytoskeleton in Hydra during morphogenesis, 52 while other studies have begun to explore the role of liquid-crystal ordering during morphogenesis 53 and in − vivo epithelial tissue patterning. 54 These findings highlight the importance of active nematic behaviours at a collective level to understand tissue shape and organization, factors central to morphogenesis. 52,53,[55][56][57][58] As such, the adaptation of cellular systems from extensile to contractile behaviours might be a crucial mechanism by which a collective living system undergoes morphological changes (sorting or tissue organiza- .…”
mentioning
confidence: 84%